2003
DOI: 10.1177/0743558403018003007
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders in the Adolescent Population:

Abstract: Adolescents become vulnerable to developing eating disorders as they mature. Very little is known about the prevalence, etiology, assessment, treatment, and outcome of eating disorders among adolescents. In general, research on eating disorders continues to be plagued with design flaws. Future studies need to be prospective research based on larger, more diverse samples of adolescents that represent all developmental stages of adolescence. Consistent diagnostic criteria and definitions of treatment interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Globally approximately 70 million people suffer from an eating disorder. Severe forms of eating disorders not only lead to physical, psychological and social distress but also result in depression Studies have shown that individuals are prone towards developing eating disorders regardless of their age, gender or ethnicity 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Globally approximately 70 million people suffer from an eating disorder. Severe forms of eating disorders not only lead to physical, psychological and social distress but also result in depression Studies have shown that individuals are prone towards developing eating disorders regardless of their age, gender or ethnicity 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid mental disorders that may provide warning signs for individuals at risk for the development of an eating disorder include: mood disorders, substance abuse and dependence, and personality disorders (APA, 2000). Specifically, a plethora of research studies displayed a predisposition to eating disorders among those diagnosed with depression (e.g., Fischer et al, 1995;Lyon & Chatoor, 1997;Moreno & Thelen, 1995;Nassar & Hodges, 1992;Pratt, Phillips, Greydanus, & Patel, 2003;Pryor & Weiderman, 1998). Proximal environmental factors also impact individual vulnerability and prognosis for recovery.…”
mentioning
confidence: 97%